Comparison of haemodynamic response to muscle reflex in heart failure with reduced vs. preserved ejection fraction. (1st November 2021) - Moriwaki, Keishi; Fujimoto, Naoki; Omori, Taku; Miyahara, So; Kameda, Issei; Ishiyama, Masaki; Sugiura, Emiyo; Nakamori, Shiro; Dohi, Kaoru
Abstract: Aims: Isometric handgrip (IHG) training reduces the blood pressure in patients with hypertension. It is unclear how IHG exercise affects the haemodynamics and cardiovascular function through the muscle reflex in patients with heart failure (HF) with reduced (HFrEF) and preserved ejection fraction (HFpEF). Methods and results: Twenty patients (HFrEF: n  = 10, HFpEF: n  = 10) underwent left ventricular (LV) pressure–volume assessments using a conductance catheter and microtip manometer to evaluate haemodynamics, LV and arterial function, and LV‐arterial coupling during 3 min of IHG at 30% of maximal voluntary contraction (MVC), followed by 3 min of post‐exercise circulatory arrest (PECA). Three minutes of IHG exercise produced significant and modest increases in the heart rate (HR) and LV end‐systolic pressure (LVESP), respectively, in both HFpEF and HFrEF groups. In HFrEF, the increase in LVESP was caused by the variable increase in effective arterial elastance (Ea), which was counterbalanced by the increase in LV end‐systolic elastance (Ees), resulting in a maintained Ees/Ea. In HFpEF, the increase in LVESP was not accompanied by changes in Ea, Ees, Ees/Ea, or LV end‐diastolic pressure. LVESP during PECA was not maintained in HFpEF, suggesting smaller metabo‐reflex activity in HFpEF. Conclusions: The IHG exercise used in this study may increase the LVESP and LVEDP without detrimental effects on cardiac function or ventricular‐arterial coupling, especially in HFpEF patients. The effects of IHG exercise on haemodynamics and ventricular‐arterial coupling may be affected by the patient background and the type and intensity of the exercise.